Comprensión e interpretación en las ciencias del espíritu: W. Dilthey. Angeles López Moreno. Universidadde Murcia, España, 1990. 195 p. - Mantilla Pineda, Benigno (Estudios de Derecho, 1991)
Comprensión e interpretación en las ciencias del espíritu: W. Dilthey. Angeles López Moreno. Universidadde Murcia, España, 1990. 195 p.